Does body mass index early in pregnancy influence the risk of maternal anaemia? An observational study in Indonesian and Ghanaian women - Martina Mocking; Ary I. Savitri; Cuno S. P. M. Uiterwaal; Dwirani Amelia; Edward Antwi; Mohammad Baharuddin; Diederick E. Grobbee; Kerstin Klipstein-Grobusch; Joyce L. Browne (BMC, 2018)
Abstract Background Anaemia is common among pregnant women, especially in low- and middle-income countries (LMICs). While body mass index (BMI) relates to many risk factors for anaemia in pregnancy, little is known about the direct relation with anaemia itself. This is particularly relevant in Southeast Asia and Sub-Saharan Africa where the prevalence of anaemia in pregnancy and the associated adverse outcomes is among the highest worldwide. This study aimed to assess the association between early pregnancy BMI and anaemia at first antenatal care visit in Indonesian and Ghanaian women. In addition, the associations between early pregnancy anaemia and adverse birth outcomes was assessed. Methods Prospective cohort studies of women in early pregnancy were conducted in Jakarta, Indonesia (n = 433) and in Accra, Ghana (n = 946), between 2012 and 2014. Linear regression analysis was used to assess relations between early pregnancy BMI and pregnancy haemoglobin levels at booking. Logistic regression analyses were used to assess associations between early pregnancy anaemia as defined by the World Health Organization (WHO) criteria and a composite of adverse birth outcomes including stillbirth, low birth weight and preterm birth. Results Indonesian women had lower BMI than Ghanaian women (23.0 vs 25.4 kg/m2, p < 0.001) and higher mean haemoglobin levels (12.4 vs 11.1 g/dL, p < 0.001), corresponding to anaemia prevalence of 10 and 44%, respectively. Higher early pregnancy BMI was associated with higher haemoglobin levels in Indonesian (0.054 g/dL/kg/m2, 95% CI 0.03 to 0.08, p < 0.001) and Ghanaian women (0.044 g/dL/kg/m2, 0.02 to 0.07, p < 0.001). Accordingly, risk for anaemia decreased with higher early pregnancy BMI for Indonesians (adjusted OR 0.88, 0.81 to 0.97, p = 0.01) and Ghanaians (adjusted OR 0.95, 0.92 to 0.98, p < 0.001). No association between anaemia and the composite of adverse birth outcomes was observed. Conclusion Higher BMI in early pregnancy is associated with higher haemoglobin levels at antenatal booking and with a reduced risk of anaemia in Indonesian and Ghanaian women.